Premature CD4+ T cell aging and its contribution to lymphopenia-induced proliferation of memory cells in autoimmune-prone non-obese diabetic mice. - Ting-Ting Sheu; Bor-Luen Chiang; Jui-Hung Yen; Wen-Chi Lin (PLoS ONE)
Lymphopenia-induced proliferation (LIP), a mechanism to maintain a constant number of T cells in circulation, occurs in both normal aging and autoimmune disease. The incidence of most autoimmune diseases increases with age, and premature CD4(+) T cell aging has been reported in several autoimmune diseases. In this study, we tested the hypothesis that premature CD4(+) T cell aging can cause autoimmune disease by examining whether premature CD4(+) T cell aging exists and causes LIP in our mouse model. Non-obese diabetic (NOD) mice were used because, in addition to Treg defects, the LIP of T cells has been shown to plays a causative role in the development of insulin-dependent diabetes mellitus (IDDM) in these mice. We found that with advancing age, NOD mice exhibited an accelerated decrease in the number of CD4(+) T cells due to the loss of naïve cells. This was accompanied by an increase in the percentage of memory cells, leading to a reduced naïve/memory ratio. In addition, both the percentage of CD28(+) cells in CD4(+) T cells and IL-2 production decreased, while the percentage of FAS(+)CD44(+) increased, suggesting that NOD mice exhibit premature CD4(+) T cell aging. This process preferentially contributed to LIP of memory cells. Therefore, our results suggest that premature CD4(+) T cell aging underlies the development of IDDM in NOD mice. Given that CD28 and IL-2 play important roles in Treg function, the relationships between premature CD4(+) T cell aging and lymphopenia as well as Treg defects in autoimmune-prone NOD mice are proposed.